Germanic heritage languages in North America : acquisition, attrition and change - Johannessen, Janne Bondi; Salmons, Joe, 1956- (Philadelphia : John Benjamins Publishing Company, 2015)
This book presents new empirical findings about Germanic heritage va rieties spoken in North America: Dutch, German, Pennsylvania Dutch, Ice landic, Norwegian, Swedish, West Frisian and Yiddish, and varieties of English spoken both by heritage speakers and in communities after langu age shift. The volume focuses on three critical issues underlying the n otion of 'heritage language': acquisition, attrition and change. The bo ok offers theoretically-informed discussions of heritage language proce sses across phonetics and phonology, morphology, syntax and semantics a nd the lexicon, in addition to work on sociolinguistics, historical lin guistics and contact settings. With this, the volume also includes a va riety of frameworks and approaches, synchronic and diachronic. Most European Germanic languages share some central linguistic features, such a s V2, gender and agreement in the nominal system, and verb inflection. As minority language faced with a majority language like English, simil arities and differences emerge in patterns of variation and change in t hese heritage languages. These empirical findings shed new light on mec hanisms and processes --
"This volume grows from recent collaboration among a group of schola rs working on Germanic immigrant languages spoken in North America, ini tially faculty and students working on German dialects and Norwegian, a nd steadily expanding since to cover the family more broadly. More stru ctured cooperation began with a small workshop at the University of Wis consin-Madison four years ago and continued with larger workshops spons ored in turn by the University of Oslo, Pennsylvania State University a nd the University of Iceland. The volume you're reading is the first gr oup publication in English (though see Johannessen and Salmons 2012 for a collection of papers on and written in Norwegian), and several other s are in preparation. Most of the papers included in this volume have g rown from the ongoing set of international workshops just sketched. The se were started by the co-editors, led initially by the first co-editor , a trajectory reflected in the relatively heavy representation of work on Norwegian. A number of the chapters have been developed specificall y from these networks and ongoing dialogues about heritage languages" - - Introduction
Includes bibliographical references and index.
Keywords: Germanic languages -- North America -- History -- Congresses; Languages in contact -- North America -- Congresses; Language acquisition -- North America -- Congresses; Germanic languages -- Influence on English -- Congresses; English language -- Influence on Germanic -- Congresses; Bilingualism -- North America -- Congresses